The Implementation of Islamic Religious Education (PAI) Learning at SDIT Al Ittihaad Tebet, Jakarta - Nurhadi, Hafidin; Setiawan, Andry; Adam, Deden Kurnia; Arifin, Bambang Samsul; Ruswandi, Uus (The Future of Education Journal, 2024)
This study examines the implementation of Islamic Religious Education (PAI) at SDIT Al Ittihaad Tebet, Jakarta, focusing on the integration of tahfidz (Qur'anic memorization) and tilawati (Qur'anic recitation) programs into the curriculum. Employing a qualitative case study design, the research explores the methods, media, and learning approaches applied in the PAI learning process. Data were collected through observations, in-depth interviews, and documentation, with subjects including teachers, students, and the school principal. Thematic analysis was used to identify key themes and insights from the data. The findings reveal that the systematic integration of tahfidz and tilawati programs strengthens Islamic values and holistically shapes students' character. These programs, designed with thematic and contextual learning approaches, incorporate Qur'anic verses into general subjects such as science and mathematics, fostering students' understanding of the synergy between Islamic teachings and modern knowledge. The study provides empirical evidence of the effectiveness of value-based learning models in integrated Islamic schools. Future research could evaluate the long-term impact of this integration on academic performance and explore the use of innovative technologies to enhance Islamic education.